Implementation of Clinical Supervision to Improve the Quality of Teacher Performance in the Learning and Teaching Process - Bidandari, Aroum; Hariyati, Nunuk (International Journal of Emerging Research and Review, 2023)
Objectives: The purpose of this study is to the advantage of clinical supervision in improving the quality of teacher performance, especially in the learning and teaching process. Method: This research carried out a systematic literature review method with a qualitative approach, allowing for the collection of data and evaluation of information from various literature sources. Results: Findings of this research according to many sources that clinical supervision can improve the quality of teacher performance.  Novelty: The novelty of this research lies in its method, namely a qualitative literature review that specifically discusses Clinical Supervision.